PERSONALIZATION AND PRIVACY IN IOT: A CONSUMER-BUSINESS CHALLENGE - Revathy Rajendra Prasad, Pramod Damle (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The need for personalization as well as the need for the right to be forgotten, puts business in deep waters. The focus of this paper is on personalization privacy of Internet of Things home devices. IoT has vast potential for marketing due to the number of connected devices and the immense amount of data that flows through it. Each device collecting distinct information about each individual connected to it and the ability to link with other devices and share the information makes it an ideal platform for marketing. With the constant requirement of the customers, business are having trouble keeping balance between privacy and personalization. The customers wish control and security over their data. Keeping their trust is of utmost importance. With the shaping of new data policies and regulations in different countries, businesses need to be careful about the collection, usage and storage of these specific data. The paper briefly discusses personalization in IoT home devices and privacy challenges. Afterwards it suggests guidelines and approaches for business to ensure the trust of consumers and to overcome the personalization-privacy paradox, keeping in mind the recent government policies for tighter data control like GDPR.